Digital Transformation Strategy for Higher Education: Soft System Methodology Analysis - Oscar Radyan Danar; Gita Zulfie Ramadhani; Dhefara Hersaning Djati; Durratun Nashihah (South Sulawesi Education Development (SSED), 2025)
Universitas Brawijaya (UB) has established itself as a leading educational institution in East Java, Indonesia, and is recognized for its diverse achievements both nationally and internationally. The importance of university rankings has become a focal point for educational institutions in Indonesia, including UB. The objective of this research is to analyze the factors affecting UB's ranking and to explore how these factors can inform better management practices within the university. This research uses the Soft System Methodology (SSM) approach, which involves the systematic analysis of real-world problems. This research involves in-depth interviews, observations, and focus group discussions (FGD) in data collection. The results of this study indicate that Universitas Brawijaya has limitations in global recognition, limitations in funding and digital research infrastructure, disparities in academic quality between units. The result for higher education management implies that it can create solutions that are not only technical but also contextual, making them easily accepted by all stakeholders. The Soft System Methodology approach allows Universitas Brawijaya (UB) to map digital transformation issues holistically and produce comprehensive solutions.